PERAN ENTREPRENEURSHIP BAGI PENGEMBANGAN KAMPUNG WISATA ORGANIK PESONA AGRO - Yogatama, Ahmad Nizar (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
Entrepreneurship necessarily present an important role for business development of Kampung Wisata Organik Pesona Agro. It is coused by the potential such as green house, organic water and fish ponds should be developed and the potential to improve production. The purpose of this study was to determine how the role of entrepreneurship and human resources could developed Kampung Wisata Organik Pesona Agro. The results showed that entrepreneurship has not contributed yet. Then, the quality of human resources of Kampung Wisata Organik Pesona Agro has its limitations as well as time management expert organic crops because it does as a side job.